Surface Treatment of Carbon Fiber Reinforced Polymer for Adhesive Bonding with Pioneer Epoxy Using Atmospheric Pressure Plasma Jet - Antipuesto, Catherine Joy Enrile (Archīum Ateneo, 2025)
A recent technique used in surface preparation for adhesive bonding is plasma treatment. In the Philippines, one of the most accessible brands of adhesive is Pioneer epoxy adhesive and, currently, there has been no existing research on the effect of plasma treatment with this adhesive. Thus, this research aims to investigate the effects of plasma pretreatment on the adhesive bonding of carbon fiber-reinforced epoxy adherents with the Pioneer epoxy adhesive. To achieve this, carbon fiber-reinforced polymers (CFRPs) samples were first plasma treated using an atmospheric pressure plasma jet (APPJ) for 0, 1, 2, and 3 min. Then, these were used to form the joint systems with three different adherent combinations. The samples were characterized using the lap shear test, contact angle measurements, optical microscope, laser microscope, and Raman spectroscopy. The result shows that the surface free energy and roughness of the CFRP increase with increasing plasma treatment time. However, the roughness is contributed by the introduction of impurities, which can weaken the bonding. Thus, when the CFRP has adhered using Pioneer epoxy adhesive, the lap shear stress (LSS) of the treated CFRP proves to be lower than that of untreated samples, with a statistically significant p-value of 0.0069. From Tukey’s honestly significant difference (HSD) test, it is concluded that plasma treating the adherent weakens the adhesive bonding of the CFRP and Pioneer adhesive joint system instead of improving it. Potential explanations for this result include the introduction of impurities by the APPJ and the presence of Mercaptan polymer in the epoxy.